The International Cooperation to Eradicate Illicit Firearms Trafficking in Southeast Asian Region - Syahmin AK; Fidelia Fidelia (Sriwijaya Law Review, 2018)
The term of illicit firearms trafficking used by the United Nations is a movement of illegal trade in firearms controlled by organised criminal groups. Such movement specifically in ASEAN region is against national and regional laws. Hence, the growth in illegal firearms trade increases concern to the Southeast Asian countries. The article aims to examine effort to eradicate illegal firearms trafficking in ASEAN countries. Statute method combined with case approach in Southeast Asian Countries is employed in this research. The findings of the research indicate that the ASEAN countries have utilized diplomatic means namely the ASEAN Regional Forum (ARF) and the establishment of ASEAN Police (ASEANAPOL). These forums propose by ASEAN Political-Security Community (APSC) in a way to coordinate among the chief of national police of ASEAN countries including, inter alia, law enforcement policies, criminal courts and transnational crimes to combat crimes committed in the ASEAN region. In fact, the effectiveness of the APSC is still in question because the illicit firearms trafficking cannot be demolished.